Imagining Oneself as Forming a Whole with Others: Descartes’s View of Love - Melanie Tate (Journal of Modern Philosophy)
In this paper, I address two widespread misconceptions about Descartes’s theory of love. Descartes defines love as a passion that ‘incites [the soul] to join in volition to the objects that appear to be suitable to it’ (AT XI: 387/Voss: 62). Several commentators assume joining in volition is an act of judgment, since forming judgments is the primary function of the will in the Meditations. However, I argue joining in volition is an act of imagining a whole one forms with an object of love. I draw on Descartes’s account of volition in The Passions of the Soul to show forming images in one’s mind qualifies as a volition, on his view. Second, commentators often assume joining in volition is an essential part of love. However, I argue joining in volition is not an essential part of love because love is not identical to joining in volition, and love does not necessitate the soul to join in volition.